Quantification and gene expression of Lactobacillus casei group species associated with dentinal lesions in early childhood caries - Ana Catarina Martins Reis; Daniela da Silva Bezerra; Erika Nikitza Shiauha Hart-Chú; Rafael Nóbrega Stipp; Sarah Florindo de Figueiredo Guedes; Beatriz Gonçalves Neves; Lidiany Karla Azevedo Rodrigues (Elsevier, 2021)
Background: Considering that the Lactobacillus casei group is strongly associated with caries progression, the use of lactobacilli as probiotics must be balanced due to their possible involvement in dental caries. Objective: This study aimed to detect and quantify L. paracasei, L. rhamnosus, and L. casei group species in the active and arrested dentinal lesions of preschoolers. It also aimed to determine the expression profiles of lactobacilli genes related to adhesion, extracellular polymeric substance regulation, and pyruvate oxidation. Methods: Total ribonucleic acid (RNA) was extracted from dentinal lesion samples (25 active, 13 arrested) of children between 2 and 5 years of age. The samples were converted to complementary deoxyribonucleic acid (cDNA), and quantitative polymerase chain reaction (qPCR) analyses were performed to quantify and determine the relative abundance (measured by percentage of total bacteria) of L. paracasei, L. rhamnosus, and L. casei group species. The expression profiles of L. paracasei/casei genes (spaC and spxB) and L. rhamnosus genes (spaE and wzb) were assessed. The Student t-test and the Mann-Whitney U test were used for comparisons. Results: The L. casei group species were found to be part of the viable microbial community in dentinal caries. L. paracasei (p = 0.001), L. rhamnosus (p = 0.022), and L. casei (p = 0.004) group species were abundant in the active dentinal lesions compared to the arrested dentinal lesions. Only the wzb gene (p = 0.006) exhibited a statistically significant difference between the active and arrested lesions in terms of its expression profile; it was expressed to a higher extent in the active dentinal lesions. Conclusions: The L. casei group species presented in large numbers in the active dentinal caries lesions, indicating that these microorganisms are related to caries activity, and the wzb gene may play an important role in caries progression.